Socio-Psychological Effects of Urban Green Areas: Case of Kirklareli City Center - Ezgi Tok; Merve Guroglu Agdas; Mete Korhan Ozkok; Azem Kuru (Journal of Contemporary Urban Affairs, 2020)
Urban open green spaces have an important role in today's health problems and the necessity for urban health to create green areas that have high accessibility for all citizens.  Acceleration of urbanization in recent decades decays balance of green areas and impervious surfaces in cities because of rent seeking society.  The main problem associated with adequate provision of green area and fair access for residents.  According to the “Spatial Planning Policy Framework” the green area per capita in urban area (10 m²), Kırklareli doesn’t provide green space per capita. The aim of the study is to identify the socio-psychological effects of the green areas in the Kirklareli. The objectives of the study is to determine the correlation between socio-psychological criteria with green space accessibility, per capita and visiting time and to discuss the findings rationale. The following hypothesis was proposed “urban green areas on inhabitants have positive effects on human health, quality of life and stress”. In this context, a survey was conducted to analyze the socio-psychological effects of urban green spaces in Kirklareli. The expected outcome of the study is that green areas are associated with positive emotions, green space per capita and accessibility that can assist to decrease inequalities in health.